Pregnancy‐associated immune‐mediated hemolytic anemia in a dog. Issue 3 (18th March 2020) - Fernandez, Yordan; Sharman, Mellora J.; Seth, Mayank
Abstract: Objective: To describe the clinical presentation, diagnostic investigations, and outcome of a dog with pregnancy‐associated immune‐mediated hemolytic anemia. Case summary: A 6‐year‐old, pregnant Bichon Frise was presented due to lethargy, inappetence, and progressive regenerative anemia with spherocytosis. The dog had been recently receiving ranitidine and amoxicillin/clavulanate. An in‐house saline agglutination test identified marked agglutination and a urinalysis identified hemoglobinuria. Thoracic and abdominal imaging, as well as infectious diseases testing, was unremarkable. The bitch started whelping shortly following hospitalization, and the anemia progressively resolved without any other intervention. Ranitidine and amoxicillin/clavulanate were re‐introduced within the following 2 months but the anemia did not reoccur. In light of these findings, a diagnosis of pregnancy‐associated immune‐mediated hemolytic anemia was made. New or unique information provided: Pregnancy‐associated immune‐mediated hemolytic anemia should be considered in female dogs that develop severe hemolytic anemia during pregnancy and may resolve spontaneously following parturition.